2014
DOI: 10.1186/1741-7007-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the chick retinal pigmented epithelium after retinal injury

Abstract: BackgroundOne of the promises in regenerative medicine is to regenerate or replace damaged tissues. The embryonic chick can regenerate its retina by transdifferentiation of the retinal pigmented epithelium (RPE) and by activation of stem/progenitor cells present in the ciliary margin. These two ways of regeneration occur concomitantly when an external source of fibroblast growth factor 2 (FGF2) is present after injury (retinectomy). During the process of transdifferentiation, the RPE loses its pigmentation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 81 publications
10
72
0
Order By: Relevance
“…The most notable difference between the gut and the RNC is the absence of SoxB1 expression during early stages of intestinal regeneration, whereas it remains expressed at the normal level in the injured radial nerve. This observation suggests that cell dedifferentiation in the gut mesothelium does not require expression of SoxB1 , which is puzzling, as Sox2, the homolog of H. glaberrima SoxB1, is not merely expressed in various vertebrate regeneration models (Christen et al, 2010; Luz-Madrigal et al, 2014; Maki et al, 2009; Perry et al, 2013), but is absolutely required for regeneration (Christen et al, 2010). The functional significance of SoxB1 down-regulation in the regenerating sea cucumber intestine is unknown and can only be determined in future experiments involving forced ectopic over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable difference between the gut and the RNC is the absence of SoxB1 expression during early stages of intestinal regeneration, whereas it remains expressed at the normal level in the injured radial nerve. This observation suggests that cell dedifferentiation in the gut mesothelium does not require expression of SoxB1 , which is puzzling, as Sox2, the homolog of H. glaberrima SoxB1, is not merely expressed in various vertebrate regeneration models (Christen et al, 2010; Luz-Madrigal et al, 2014; Maki et al, 2009; Perry et al, 2013), but is absolutely required for regeneration (Christen et al, 2010). The functional significance of SoxB1 down-regulation in the regenerating sea cucumber intestine is unknown and can only be determined in future experiments involving forced ectopic over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in redox status were documented by measuring levels of immunofluorescence when using an antibody against 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) which covalently binds to oxidized adducts in proteins. Previous work in our laboratory determined that activation of transcription factors necessary for induction of regeneration occurs in response to injury by 6 hours (h) post-retinectomy (PR) (Luz-Madrigal et al, 2014). Therefore, we investigated changes in the redox status within the CM at both 6h PR and 24h PR to be certain measurements were within the window of induction.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, several non-mammalian vertebrates, including the chick, have the potential to regenerate their entire retina from endogenous cell populations after retinal damage Luz-Madrigal et al, 2019 4 [4,5]. The embryonic chick can regenerate its retina at embryonic day (E) 4-4.5 (stages 23-25; [6,7]) by reprogramming cells of the retinal pigment epithelium (RPE) into retina progenitor cells that eventually differentiate into the major retinal cell types [8][9][10][11]. We previously demonstrated that during the Phase I of RPE reprogramming, within 6 hours after surgical removal of the retina (retinectomy), the quiescent cells of the RPE transiently reprogram (these cells are referred to as transient reprogrammed RPE, t-rRPE), and express pluripotency inducing factors including sox2, c-myc, klf4, and eye field transcription factors (EFTF), while simultaneously down-regulating RPE specific markers [11].…”
Section: Introductionmentioning
confidence: 99%